2018
DOI: 10.21608/jpp.2018.36350
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Yield Components of Some Sugar Cane Varieties (Saccharum officinarum L.) as affected by Different Nitrogen Fertilization Levels

Abstract: Two field trials were conducted during two successive growing seasons of 2016/2017 and 2017/2018 at Mallawy Agricultural Research Station, Agricultural Research Center, El-Minia Governorate (Middle Egypt) to study the effect of different levels of Nfertilization (160,190 and 220 kg /fed) on yield, yield components and quality of five sugar cane varieties (G.T.54-9(C9), G.2003-47, G.99-103, G.2004-27 and G.2010-7). A split plot design with three replications was used, main plots were represented by five sugar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
3
1
0
Order By: Relevance
“…The variation between the examined varieties in brix percentage may be due to the differences in growth and response to the surrounding environmental conditions prevailing during the formation of soluble solids in the cane plants. These results confirmed with those obtained by El-Shafai and Ismail (2006), Mehareb et al (2018) and Abd El-Azez et al (2018). Found that brix % was significantly affected by the examined sugar cane varieties.…”
Section: Results and Discussion 1-brix Percentagesupporting
confidence: 91%
See 3 more Smart Citations
“…The variation between the examined varieties in brix percentage may be due to the differences in growth and response to the surrounding environmental conditions prevailing during the formation of soluble solids in the cane plants. These results confirmed with those obtained by El-Shafai and Ismail (2006), Mehareb et al (2018) and Abd El-Azez et al (2018). Found that brix % was significantly affected by the examined sugar cane varieties.…”
Section: Results and Discussion 1-brix Percentagesupporting
confidence: 91%
“…Ahmed (2003). This result is in agreement with those obtained by Mohamed et al (2012), Kumara and Bandara (2002), Sohu et al (2008) and Abd El-Azez et al (2018). Who found that sucrose percentage was differed significantly by the tested sugar cane varieties.…”
Section: -Sucrose Percentagesupporting
confidence: 92%
See 2 more Smart Citations